STRATEGI PEMASARAN AGEN ASURANSI PRULINK SYARIAH DI KABUPATEN JEPARA - Edi Susilo; Maghfirotun Nikmah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
This study aims to analyze insurance agent marketing strategies to get new customers of Sharia Prulink Insurance in Jepara Regency. The study used descriptive analytical qualitative methods. Data obtained by observation, interviews, literature studies, documentation, data processing, data presentation, and conclusions. The results of the study show that the insurance agent's strategy to get new customers is to maintain a cycle: Planning, Prospects, Approaches, Fact Finding, Presentation, Dealing with objections and Closing. To maintain and improve customers, insurance agents take steps: know your costomer (KYC), visit customers regularly; explain the benefits of insurance, serve excellence, willingness to serve customers who need help for their insurance, and awards on customers' birthdays.